Understanding the effects of isolation on seed and pollen flow, spatial genetic structure and effective population size of the dioecious tropical tree species Myracrodruon urundeuva - Gaino, Ana P. S. C. [UNESP]; Silva, Alexandre M. [UNESP]; Moraes, Marcela A. [UNESP]; Alves, Patricia F. [UNESP]; Moraes, Mario L. T. [UNESP]; Freitas, Miguel L. M.; Sebbenn, Alexandre M. [UNESP] (Springer, 2010)
This study examines the levels of gene flow, the distance and the patterns of pollen and seed dispersal, the intra-population spatial genetic structure (SGS) and the effective population size of a spatially isolated Myracrodruon urundeuva population using five microsatellite loci. The study was carried out in the Paulo de Faria Ecological Station, São Paulo State, Brazil and included the sampling and mapping of 467 adult-trees and 149 juveniles. Open-pollinated seeds (514) from 29 seed-trees were also sampled and genotyped. Significant SGS was detected in both adult (S(p) = 0.0269) and juveniles trees (S(p) = 0.0246), indicating short-distance seed dispersal. Using maternity analysis, all juveniles had the mother-tree assigned within the stand. A father-tree within the stand was also assigned for 97.3% of the juveniles and 98.4% of offspring. The average pollen dispersal distance measured in juveniles ((delta) over cap = 138 +/- 169 m, mean +/- SD) and off-spring ((delta) over cap = 252 +/- 204 m) were higher than the average seed dispersal distance measured in juveniles ((delta) over cap = 124 +/- 150 m). About 70% of the pollen from juveniles and 51% from offspring traveled less than 200 m and, 72% of the seeds traveled less than 50 m. The effective population size of the studied sample indicates that the 467 adult- trees and 145 juveniles correspond respectively to 335 and 63 individuals that are neither inbred nor relatives. The results are discussed in relation to their impact on seed collection practices and genetic conservation.
Keywords: Myracrodruon urundeuva; Tropical tree species; Microsatellite loci; Seed dispersal; Pollen dispersal; Spatial genetic structure